2021
DOI: 10.3889/oamjms.2021.7111
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Children School Meal using Meal Report at Kindergarten School in Indonesia: A Quasi-Experimental Study

Abstract: BACKGROUND: Kindergarten children are prone to be stunted. Currently, most kindergarten school run school meal program. AIM: The aim of the study was to assess the effect of school meal report on the meal performance. METHODS: The study was a Quasi Experiment. Four kindergarten schools were selected; two schools as intervention study and the other two schools as the control group. We enrolled 106 mothers. There were five items of food performance to be scored from 6 to 10. While children in the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similar findings can be found in Sinaga's research. He has proven that using scores raport was effective to motivate mothers provide better meals for school children (Sinaga et al, 2021).…”
Section: Benefits Of Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings can be found in Sinaga's research. He has proven that using scores raport was effective to motivate mothers provide better meals for school children (Sinaga et al, 2021).…”
Section: Benefits Of Activitiesmentioning
confidence: 99%
“…Taking food to school is a program for most kindergarten schools. A research on several kindergarten children found thatmost children bring fried rice, fried noodles, 71 omelettes, fried fish (Sinaga et al, 2021). Packaged food and stall snacks are also used as food supplies for children even though these types of food generally contain chemical preservatives (Handriana Gustin .J, 2020).…”
Section: Introductionmentioning
confidence: 99%